2021
DOI: 10.1177/0148558x211004134
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Principal Market Determination: Fair Value Measurement of Cryptocurrency

Abstract: Cryptocurrencies and blockchain technology are disruptive innovations at the vanguard of a new wave of the digital revolution. The far-reaching appeal, global reach, unprecedented mobility of capital, and multitude of trading venues have created a marketplace like no other. The economic fundamentals underlying this market are yet to be fully comprehended, as evidenced by the often-contradicting guidelines recommended by accounting firms, government agencies, and standard setters. Many of the definitions and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…, 2019). In addition, Beigman et al. (2021) introduced a method to identify the primary market for fair value measurement as per IFRS 13, and Beigman et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2019). In addition, Beigman et al. (2021) introduced a method to identify the primary market for fair value measurement as per IFRS 13, and Beigman et al.…”
Section: Resultsmentioning
confidence: 99%
“…Morozova et al, 2020). Within the (D3) category, three studies (Beigman et al, 2021(Beigman et al, , 2023Ram et al, 2016) utilizing a mixed methodology were incorporated and classified as "other empirical. "…”
Section: Exploring the Uncharted Territoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, cryptos fall under the accounting rules for “Intangible assets with indefinite useful lives” (IAS 38.107), so they cannot be amortized but only impaired. Furthermore, if an active market exists, then intangible assets can be valued at fair value (IAS 38.75) (Procházka, 2018; Morozova et al , 2020; Beigman et al , 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A great share of studies examines the correlation between cryptocurrency prices and their underlying fundamental value (Biais et al, 2020;Athey et al, 2016;Zimmerman, 2020;Cong et al, 2021;Liu and Tsyvinski, 2021). While some works have suggested that bitcoin lacks a fundamental value and is purely speculative (Cheah and Fry, 2015;Kallinterakis and Wang, 2019), others argue that cryptocurrencies, as a whole, possess a fundamental value, albeit one that is challenging to ascertain (Dowd, 2014;Beigman et al, 2021).…”
Section: Risk-return Relationshipmentioning
confidence: 99%